2022
DOI: 10.1136/rmdopen-2022-002424
|View full text |Cite
|
Sign up to set email alerts
|

Association between different infection profiles and one-year outcomes in ANCA-associated vasculitis: a retrospective study with monthly infection screening

Abstract: ObjectivesThis study aimed to explore clinical features of early infection in patients with antineutrophil cytoplasmic antibody-associated vasculitis (AAV) and to identify the association between the infection profile of patients with AAV during the first 3 months and 1-year survival.MethodsA total of 415 newly diagnosed patients with AAV in the Department of Nephrology at Shanghai Ruijin Hospital from 2000 to 2018 were included. Four Cox regression models were used to analyse the association based on demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
2
2
Order By: Relevance
“…Furthermore, nearly half of the patients with MPA received cyclophosphamide, and one‐third received PLEX, revealing a disease activity requiring aggressive treatment. In previous literature, different prognostic factors of mortality, including age, disease activity, infection, organ damage, and interstitial lung disease, have been proposed 19–24 . However, high proportions of kidney involvement, higher initial creatinine levels, and PLEX treatment were noted in our patients, which suggests renal involvement is the main contributing factor of morality in this study.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, nearly half of the patients with MPA received cyclophosphamide, and one‐third received PLEX, revealing a disease activity requiring aggressive treatment. In previous literature, different prognostic factors of mortality, including age, disease activity, infection, organ damage, and interstitial lung disease, have been proposed 19–24 . However, high proportions of kidney involvement, higher initial creatinine levels, and PLEX treatment were noted in our patients, which suggests renal involvement is the main contributing factor of morality in this study.…”
Section: Discussioncontrasting
confidence: 66%
“…In previous literature, different prognostic factors mortality, including age, disease activity, infection, organ damage, and interstitial lung disease, have been proposed. [19][20][21][22][23][24] However, high proportions of kidney involvement, higher initial creatinine levels, and PLEX treatment were noted in our patients, which suggests renal involvement is the main contributing factor of morality in this study.…”
Section: Discussioncontrasting
confidence: 49%
“…In a recent study of Xu et al, infections were shown to be the most important cause of mortality in AAV patients in the first year of diagnosis. 21 This showed us that we should be more careful in terms of infection, especially in the first year of induction therapy.…”
Section: Discussionmentioning
confidence: 99%
“…HCQ has previously been shown to have a beneficial effect in lowering blood sugars [166][167][168] , improving lipid profiles [167,168] , and reducing atherosclerosis/improving vascular elasticity [150,151] all of which improve CV risk profiles [169] .…”
Section: Improved Cardiovascular Riskmentioning
confidence: 99%